(untitled) (Psychology Travelogs, 2025)
The article reveals the importance of self-regulation as a key psychological competence of the future social worker in the context of professional training in higher education institutions. Based on the analysis of modern scientific approaches and research, it has been substantiated that the formed skills of emotional, behavioral and cognitive self-regulation are a necessary condition for the effective performance of professional duties in difficult social conditions. The main mechanisms of self-regulation development are characterized, in particular self-reflection, self-motivation, and stress control, which collectively ensure the student’s ability to consciously analyze and adjust their emotional responses, sustain a consistent level of internal motivation toward professional goals despite external challenges, and maintain psychological stability and resilience necessary for effective functioning in emotionally demanding social work environments. Particular attention is paid to the role of psychological self-regulation in the conditions of practical training and internship, which contribute to the transition from theoretical understanding to the application of self-regulatory strategies in real professional situations. The article presents psychological and pedagogical conditions that contribute to the formation of self-regulation, including: the creation of a psycho-emotionally safe educational environment, the implementation of training technologies, the development of a reflective culture, the organization of psychological support, as well as the formation of motivational readiness for self-development. A connection is established between the level of self-regulation development and the professional stability of the future social worker, which confirms the importance of self-regulation as a resource for preventing emotional burnout and strengthening readiness for long-term activity in the field of social work. Prospects for further research are seen in improving methodological tools for assessing self-regulation, developing special educational programs aimed at its development, as well as in an interdisciplinary analysis of the phenomenon of self-regulation in the context of professional training of social workers.